Dynamic Patterns of Histone Methylation Are Associated with Ontogenic Expression of the Cyp3a Genes during Mouse Liver Maturation - Ye Li; Yue Cui; Steven N. Hart; Curtis D. Klaassen; Xiao Zhong (2009)
Human cytochrome P450 3A (CYP3A) members are major drug-metabolizing enzymes in the liver. Two genes, CYP3A4 and CYP3A7, exhibit a developmental switch in gene expression during liver maturation. CYP3A4 is mainly expressed in adults, whereas CYP3A7 is dominantly expressed during the fetal and neonatal stages. Their ontogenic expression results in developmentally related changes in the capacity to metabolize endogenous and exogenous compounds. Thus, it is desirable to understand the mechanisms controlling the developmental switch. Mice also exhibit a developmental switch between Cyp3a16 (neonatal isoform) and Cyp3a11 (adult isoform) and may serve as a model to study the mechanisms controlling the developmental switch. Because the epigenetic code (e.g., DNA methylation and histone modifications) is implicated in regulating gene expression and cellular differentiation during development, the current study determined the status of DNA methylation, histone-3-lysine-4 dimethylation (H3K4me2) and histone-3-lysine-27 trimethylation (H3K27me3) around the mouse Cyp3a locus at various developmental ages from prenatal, through neonatal, to young adult. DNA was not hypermethylated in the Cyp3a locus at any age. However, increases in Cyp3a16 expression in neonatal livers and Cyp3a11 in adult livers were associated with increases of H3K4me2. Suppression of Cyp3a16 expression in adult livers coincided with decreases of H3K4me2 and increases of H3K27me3 around Cyp3a16. In conclusion, histone modifications of H3K4me2 and H3K27me3 are dynamically changed in a locus-specific manner along the Cyp3a locus. Developmental switch between Cyp3a11 and Cyp3a16 gene expression seems to be due to dynamic changes of histone modifications during postnatal liver maturation.